If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6y = -44 Solving 5x + -6y = -44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 5x + -6y + 6y = -44 + 6y Combine like terms: -6y + 6y = 0 5x + 0 = -44 + 6y 5x = -44 + 6y Divide each side by '5'. x = -8.8 + 1.2y Simplifying x = -8.8 + 1.2y
| 6+3=5 | | 4squared-20x+24=0 | | 2x-3-3x+7x=5x | | 19/152 | | 15-28=3x+(4y) | | 9(y+1)= | | -4x+14=64 | | 2x-17=5+3x | | xa-bc=0 | | D=3x | | 1x-3y=3 | | 33=42-w | | ax-bc=0 | | 5x+2(x-1)=8 | | 0.3x-.24=0.42+.52x | | 4=2(3y-7) | | -3(4x+3)+4(16x+1)=43 | | 3^-4x/5=.0019 | | N^2+3n-162=0 | | X^3-15x^2-15x=16 | | 40=32+v | | 2x^2-x+2=-3 | | 7/11x=17 | | 14x+4x+90=180 | | 2(u-6)=9u-19 | | 2x-40=-6 | | 1.5x-5=1.2x+8 | | 45+5y=-x | | 7x^2-0.4x+0.04=0 | | 5x^2+8xy+3y^2=0 | | 4n-28/3=3 | | 18=3(4x-6) |